International human resource management - Özbilgin, Mustafa; Groutsis, Dimitria; Harvey, William S. (Melbourne, VIC, Australia ; New York : Cambridge University Press, 2014)
International Human Resource Management offers a contemporary and multilayered introduction to international and comparative human resource management for university study. It critically analyses the core issues and emerging trends in the field, with a consistent emphasis on real-world scenarios and concerns. At the macro level, the book examines how IHRM fits within and adapts to the ever-changing environment of international relations and global development. At the firm level, it elucidates the strategic goals served by IHRM and the processes used to achieve them. At the individual level, the analysis extends beyond the traditional focus on expatriates to encompass the various IHRM actors and their motivations. Each chapter features a case study, tutorial activities and discussion questions. The book concludes with three extended case studies, each based on a specific region, to help students consolidate their understanding.
Title from publisher's bibliographic system (viewed on 12 Aug 2019).
Keywords: elektronické knihy; electronic books; International business enterprises -- Personnel management; Personnel management